De “herederos y corajudos”: La imagen pública de la docencia en la prensa gráfica argentina - Iglesias, Andrea (Universidad de Costa Rica, 2019)
The following article presents the conclusions of a completed research in which we analyzed the construction of the public image of secondary school teachers in the Argentine graphic press. Although the problem of teaching has taken visibility in the mass media in recent years in the countries of the region, we consider that our object of study hasn’t been enough explored in the field of education. According to this, in the context of compulsory secondary education in Argentina and the expansion of the higher level in the region, we analyzed here whether the training and performance of these professors are newsworthy elements, considering that the press constructs representations that become part of the public agenda and influence the perception of the audience. From a qualitative approach and an interdisciplinary perspective that combines elements of historiography, media sociology and critical discourse analysis, we carried out a comparative analysis of a 530 articles corpus of the three most important national newspapers (La Nación, Clarín and Página 12) between 2000 and 2013. The outcomes indicate that the training and performance of teachers are present in the media agenda. We conclude that most newspapers build a discredited and devalued image of the teaching work. This research brought to us the ways in which the graphic press builds a discourse that delegitimizes the profession. The study of the way in which these constructions influence on the teaching career remains outstanding